Pengaruh Pemberian Ekstrak Daun Kelor (Moringa oleifera) untuk Menghambat Infeksi Bakteri Aeromonas hydrophila pada Ikan Nila (Oreochrromis niloticus) - Anisa, Nani; Taufieq. S, Nur Anny; Indrayani, Indrayani (Agricultural Technology Education Study Program, 2024)
This study aims to analyze the effect of administration and concentration of using moringa leaf extract on Aeromonas hydrophila bacterial infection in tilapia (Oreochromis niloticus). The benefit of this study is to provide information that the use of moringa leaf extract as an inhibitor of Aeromonas hydrophila bacterial infection in tilapia. The research method used was a completely randomized design with 4 treatments and 3 repetitions for each treatment, as for the treatment used namely the use of moringa leaf extract 0 mg/l (K), 50 mg/l (A), 65 mg/l (B) dan 80 mg/l (C). The variables observed in this study were fish behavior, fish morphology, fish gills, fish survival, and water quality parameters (temperature, pH, DO and ammonia). Data was processed using the SPSS program with the Kruskal-Wallis H analysis technique and then the PostHoc test was carried out. The results showed that the administration of moringa leaf extract had an effect on tilapia in inhibiting Aeromonas hydrophila bacterial infection in tilapia where the best use of the extract was 80 mg/l (C) with changes in anatomy, morphology and behavior of fish which were getting better after administration of the extract.